Revitalisasi Pendidikan Karakter dalam PAI sebagai Upaya Pencegahan Radikalisme pada Remaja - Asraf Kurnia; Martin Kustati; Nana Sepriyanti; Siti Aisyah; Vegia Oviensy (Institut Muslim Cendekia, 2024)
Radicalism among teenagers has become an increasingly pressing issue in Indonesia, especially with the significant influence of digital technology that facilitates the rapid spread of radical ideologies. In this context, character education within Islamic Religious Education (PAI) can be an effective solution to prevent radicalization. This article discusses the importance of revitalizing character education in PAI as an effort to prevent radical influences on teenagers. By integrating values such as tolerance, justice, and religious moderation, character education in PAI not only focuses on cognitive aspects but also on the formation of attitudes and behaviors that align with national values. Value-based and contextual character education is expected to shape a generation of young people who are tolerant, have integrity, and love their country. Furthermore, the collaboration between schools, families, and communities is essential to create an environment that supports the development of positive character in teenagers. With this approach, revitalizing character education in PAI can strengthen teenagers' resilience against radicalization and help shape individuals with noble character and responsibility toward the nation and the state.